A Short Satisfaction Questionnaire for an Independent Medical Examination: A pilot study. (Global Journal of Medical Research, 2023)
Objective This study was conducted to develop and validate a questionnaire to assess client satisfaction with an Independent Medical Examination IME Design The questionnaire IMESQ was developed as a short assessment of six items covering six domains relevant to an IME The sample was tested for internal consistency reliability Construct validity of the questionnaire was via a parallel measurement analysis Participants Data were collected from 76 adult respondents male 44 7 mean age 42 9 13 3 years Results The questionnaire had good correlation of paired items range r 0 55 to 0 80 M 0 65 The Cronbach s value of the questionnaire was 91and the spit-halves reliability was 90 suggesting good internal consistency There was strong correlation rs 82 with a numerical satisfaction scale NSS Compared with a Surrogate score calculated from the NSS the intrarater reliability was high ICC 75 A Bland-Altman analysis identified 14 Outliers who underrated or overrated the responses to the questionnaire
Keywords: pilot study; independent medical examination; satisfaction questionnaire; internal consistency; valida-tion; intrarater